Proposed attack strategy for nugget product of pt bernas mulia sakti to increase comapny's revenue - Amril Putri, Farrah; Toha, Muhammad (The Indonesian Journal of Business Administration, 2018)
Abstract. Introduction:   PT Bernas Mulia Sakti (PT BMS) is one of the strategic player in broiler industry. For the last five years, sales of PT BMS has been increasing moderately by averagely 7.6%. Nevertheless, the profit tends to be fluctuating at 5.9% within the same periods. In order to prevent further fluctuation in the upcoming periods, board of directors comes up with the agreement to innovate with new product, called product diversification. The firm desires to improve profit in the near future, and it can be achieved by product diversification as relying on existing product means relying on purchasing power of the current market share. Grabbing new market share would be an option, but it would lead to less-efficient cost.  Methods: The research done has survey-based analysis, Porter’s Generic Strategy, The Five Major Element Strategy, Strategy Moves Attack Strategy and Proposed Business Model Canvas. Results: The first fact is that most of chicken nugget consumers are millennial generation by 83%. Therefore, PT BMS would compete in the market using non-price approach which is positioning as healthy chicken nugget. Conclusion: In executing differentiation business strategy, PT BMS technically implements bypass attack strategy considering that it is relevant in introducing new product to a market with strong competition, as well as attempting to cover new service that competitors do not actually cover. With the bypass attack strategy, PT. BMS identifies which aspects of the competitor that can be indirectly attacked, which are (1) competitor’s product still uses preservatives therefore it would be strong positioning for Nuggetin as healthy chicken nugger; (2) competitors sell frozen product which reduce the quality of the taste, while Nuggetin offers home delivery service for fresh product; and (3) proactive after-sales service including consultation services for customers in terms of living healthily. That way PT BMS is expected to improve its sales performance in the future. Keywords:  Attack Strategy, Broiler Industry, Diversification Product, New Market, New Product